International fieldschool reciprocity: using a whole-of-university approach to create positive change in Northern Uganda. Issue 7 (10th November 2019) - Munro, Paul G.; Bartlett, Anne L.; Dhizaala, James T.; Laloyo, Stella Apecu; Oswin, Sebastian Oguti; Walker, Sarah
ABSTRACT: International fieldschools to developing countries have become an important component of the university curriculum because they provide experiential learning and research skills, while also contributing a range of soft skills such as resilience, empathy, resourcefulness, critical thinking, and cross-cultural communication. Yet, with the increasing popularity of 'developing world' fieldschools, an ever-more pertinent question to ask is, cui bono ? Who benefits when relatively 'privileged' students from wealthy countries travel to visit 'underprivileged' communities in poorer parts of the world? In this article, we contribute to the discussion about fieldschool reciprocity using data from a newly established program in Northern Uganda, established as part of the University of New South Wales' UNSW2025 strategy. We show that a whole-of-university approach has significant benefits for staff and students from both institutions, more diffuse benefits for the wider Ugandan host community, as well as the potential to create synergies to leverage community transformation. We also look at challenges that include: power differentials, uncertainty in the field environment, sustainability, and the ability to maintain collaborative equity between institutions over the long term.